2015
DOI: 10.1038/nmat4175
|View full text |Cite
|
Sign up to set email alerts
|

A design strategy for intramolecular singlet fission mediated by charge-transfer states in donor–acceptor organic materials

Abstract: The ability to advance our understanding of multiple exciton generation (MEG) in organic materials has been restricted by the limited number of materials capable of singlet fission. A particular challenge is the development of materials that undergo efficient intramolecular fission, such that local order and strong nearest-neighbour coupling is no longer a design constraint. Here we address these challenges by demonstrating that strong intrachain donor-acceptor interactions are a key design feature for organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
490
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(521 citation statements)
references
References 47 publications
26
490
2
3
Order By: Relevance
“…S18-S21), resulting in a long-lived signature that closely matches the features observed under direct excitation (Fig. 4C, Bottom) (26,27). The remarkably sharp triplet absorption features we observe for the triplet exciton have been observed in a small set of other systems (18,28), where the rigidity of the molecule gives narrow absorption bandwidths, and are a distinct advantage of solution studies of acenes compared with the solid state.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…S18-S21), resulting in a long-lived signature that closely matches the features observed under direct excitation (Fig. 4C, Bottom) (26,27). The remarkably sharp triplet absorption features we observe for the triplet exciton have been observed in a small set of other systems (18,28), where the rigidity of the molecule gives narrow absorption bandwidths, and are a distinct advantage of solution studies of acenes compared with the solid state.…”
Section: Resultssupporting
confidence: 74%
“…In this case, the sharp features allow us to distinguish the absorption signatures of the three species, and in particular track the evolution of the excimer to the triplet excitons. The sensitization measurement also enabled a determination of the triplet absorption cross-section of 5,400 Lmol −1 cm −3 at 1.63 eV, based on the degree of quenching of the triplet excitons on the sensitizer by TIPS-tetracene (27). This value was used to obtain a triplet exciton yield of 120% ± 20% of the singlet exciton concentration.…”
Section: Resultsmentioning
confidence: 99%
“…These authors have obtained nearly identical results for a different DA copolymer PDTP-DFBT [27]. Busby et al have reported triplet exciton generation in picosecond (ps) time scale from a transient absorption measurement of the DA copolymer PBTDO1 [28]. The transient absorption observed is the equivalent of the higher energy PA 2 absorption of Huynh et al [26] (see Fig.…”
mentioning
confidence: 77%
“…In singlet fission, one high energy singlet excited state can decay to form two triplet excitons and is well known to be nearly 100% efficient in many molecule systems. [24,[31][32][33][34][35] This process is thermodynamically endothermic if the triplet energy is less than or equal to the singlet energy, providing the minimum emission wavelength (870 nm), and corresponding PV bandgap, requirement. In this case the UV-only efficiency limits (with emission in the NIR and SF) increases from 3.7% to 5.6% as shown in Figure 4b.…”
Section: Ideal Transparent Luminescent Solar Concentrator Case Imentioning
confidence: 99%